Municipal Companies as Facilitators of Smart and Sustainable Regional Development Policy (SmartRegion) - Siemiątkowski, Piotr (Historia i Polityka, 2025)
This article presents the role of municipal companies in fostering smart and sustainable regional development (SmartRegion). Drawing from prominent literature in the field, the analysis covered this type of entities. The case study evaluated whether municipal companies in the Kuyavian-Pomeranian region of Poland align with the principles of smart regional development. A pilot study was conducted to identify noteworthy initiatives that extend beyond the jurisdiction of individual local governments while leveraging regional potential to enhance the area’s overall attractiveness through optimized municipal policies. The municipal companies highlighted in this article, informed by international best practices and their own operational expertise, are engaged in ambitious initiatives that effectively contribute to the region’s smart and sustainable development policy. Beyond acquiring knowledge, these entities are progressively implementing innovative solutions they have developed. This trend, supported in part by recommendations from European Union programs, is expected to gain further momentum.